Predicting behavioral and brain markers of inhibitory control at preschool age from early measures of executive attention - Conejero, Ángela; Rico-Picó, Josué; Moyano, Sebastián; Hoyo, Ángela; Rueda, M. Rosario (Frontiers in Psychology, 2023)
Inhibitory Control (IC) is the ability to prevent prepotent responses when inappropriate. Longitudinal research on IC development has mainly focused on early childhood and adolescence, while research on IC development in the first years of life is still scarce. To address this gap in the literature, we explored the association between executive attention (EA) and elementary forms of IC in infancy and toddlerhood with individual differences in IC later at 5 years of age. We conducted a five-wave longitudinal study in which children’s EA and IC (n=96) were tested at the age of 9 and 16 months, and at 2, 3, and 5 years. We expected that EA skills in infancy and toddlerhood would be related to better performance of children on IC tasks, together with a more mature inhibition-related brain functioning. Children performed a variety of age-appropriate EA and IC tasks in each wave measuring inhibition of attention, endogenous control of attention, inhibition of the response and conflict inhibition. At age 5 years, IC was measured with a Go/No-go task while recording event-related potentials. After correlation analyses, structural equation model analyses were performed to predict IC at 5 years of age from EA and early IC measures. Results revealed that EA at 9 months predicted IC measures at 2 years of age. Likewise, measures of IC at 2 years predicted performance on the Go/No-go task at behavioral and neural levels. No direct association between EA at 9 months and IC at 5 years of age was found. We further observed that some EA and IC measures were not associated across time. Altogether, results indicate that IC in early childhood could be predicted from EA and IC at 9 months and 2 years of age and suggest that the early emergence of IC relies on the development of particular EA and basic IC skills. However, some discontinuities in the longitudinal development of IC are observed in the first 5 years of life. These findings provide further support for the hierarchical model of IC development.